Engineering mechanics - Goyal, M. C. (PHI Learning, 2011)
This textbook, now in its Second Edition, continues to provide a thorough understanding of the basic concepts of mechanics. It has a structured format with a gradual development of the subject from simple concepts to advanced topics so that the students are able to comprehend the subject with ease.